Consensus opinion on diagnosis and management of thrombotic microangiopathy in Australia and New Zealand. Issue 6 (12th June 2018) - Fox, Lucy C.; Cohney, Solomon J.; Kausman, Joshua Y.; Shortt, Jake; Hughes, Peter D.; Wood, Erica M.; Isbel, Nicole M.; de Malmanche, Theo; Durkan, Anne; Hissaria, Pravin; Blombery, Piers; Barbour, Thomas D.
Abstract: Thrombotic microangiopathy (TMA) arises in a variety of clinical circumstances with the potential to cause significant dysfunction of the kidneys, brain, gastrointestinal tract and heart. TMA should be considered in all patients with thrombocytopenia and anaemia, with an immediate request to the haematology laboratory to look for red cell fragments on a blood film. Although TMA of any aetiology generally demands prompt treatment, this is especially so in thrombotic thrombocytopenic purpura (TTP) and atypical haemolytic uraemic syndrome (aHUS), where organ failure may be precipitous, irreversible and fatal. In all adults, urgent, empirical plasma exchange (PE) should be started within 4–8 h of presentation for a possible diagnosis of TTP, pending a result for ADAMTS13 (a disintegrin and metalloprotease thrombospondin, number 13) activity. A sodium citrate plasma sample should be collected for ADAMTS13 testing prior to any plasma therapy. In children, Shiga toxin‐associated haemolytic uraemic syndrome due to infection with Escherichia coli (STEC‐HUS) is the commonest cause of TMA, and is managed supportively. If TTP and STEC‐HUS have been excluded, a diagnosis of aHUS should be considered, for which treatment is with the monoclonal complement C5 inhibitor, eculizumab. Although early confirmation of aHUS is often not possible, except in the minority of patients in whom auto‐antibodies against factor H are identified, genetic testing ultimately reveals a complement‐related mutation in a significant proportion of aHUS cases. The presence of other TMA‐associated conditions (e.g. infection, pregnancy/postpartum and malignant hypertension) does not exclude TTP or aHUS as the underlying cause of TMA.